Calm in the Storm: Emily Oster's Parenting Newsletter During COVID-19. Issue 1 (2nd January 2022) - Murray, Margaret
Abstract: This article examines one new media source that was shared in the Academic Mothers Facebook group: Emily Oster's parenting newsletter. Oster's newsletter specifically focused on parental decision making during the COVID-19 pandemic. This article focuses on the messages and themes in the newsletter during the first six months of the pandemic in the United States. That time was marked by new and increased uncertainty for parents around family health and well-being, creating a particular need for parenting information and advice. Through critical rhetorical criticism, five main themes emerged from an analysis of the newsletter: disruption, process-centered decision making, a recentering of parents, strong but moderated emotion, and a call for collective action. Overall, Oster's newsletter rejects intensive mothering and parental determinism by offering more nuanced parental decision making. This is particularly important for mothers because they bear a disproportionate share of the parenting load, especially regarding risk.